Pluripotent Stem Cell Therapies for Parkinson Disease: Present Challenges and Future Opportunities - Kim, Tae Wan; Koo, So Yeon; Studer, Lorenz (Frontiers in Cell and Developmental Biology, 2020)
In Parkinson’s disease (PD), there are currently no effective therapies to prevent or slow down disease progression. Cell replacement therapy using human pluripotent stem cell (hPSC)-derived dopamine neurons holds considerable promise. It presents a novel, regenerative strategy, building on the extensive history of fetal tissue grafts and capturing the potential of hPSCs to serve as a scalable and standardized cell source. Progress in establishing protocols for the direct differentiation to midbrain dopamine neurons from hPSC have catalyzed the development of cell-based therapies for PD. Consequently, several groups have derived clinical-grade midbrain dopamine neuron precursors under cGMP condition, which are progressing towards clinical testing in PD patients. Here we will review the current status of the field, discuss the remaining key challenges, and highlight future areas for further improvements of hPSC-based technologies in the clinical translation to PD.